Health literacy and eating-related behaviors stratified by the presence of comorbidities in public Brazilian school teachers (Revista Contexto & Saúde, 2025)
This study aimed to analyze the cross-sectional association between health literacy and eating-related behaviors (usage of nutrition labels and eating behaviors) in public school teachers, from a large city in southern Brazil. Health literacy was assessed using the Newest Vital Sign instrument. Poisson regression models were adjusted for sociodemographic covariates, and the analysis was stratified by the presence of obesity, hypertension, diabetes, and dyslipidemia. Among the 961 schoolteachers studied, 37.0% were classified as having adequate health literacy. Adequate health literacy was associated with more frequent verification of calories (results given in relation to prevalence ratio and confidence interval 95%: 1.34; 1.13-1.58), sodium (1.27; 1.11-1.46), unsaturated fat (2.36; 1.53-3.65) and trans fat (1.81; 1.39-2.36), more frequent use of such information to guide food consumption (1.23; 1.02-1.49), as well as lower frequent consumption of ultra-processed food (0.62; 0,41-0.93). However, adequate health literacy was also associated with a lower frequency of checking sugars or simple sugars (0.53; 0.33-0.87) on food labels, a higher prevalence of frequent consumption of sweetened carbonated beverages (1.23; 1.03-1.64), while failed to correlate with important healthy eating-related behaviors, such as consumption of fruits and vegetables. Analysis stratified by the presence of comorbidities suggest that adequate health literacy was associated with consulting only a few items on food labels and showed few associations with eating habits. These results suggest that, at least for school teachers, health literacy has a discrete association on information seeking and eating habits.
Keywords: Alfabetización en Salud; conductas alimentarias; verificación de información nutricional